Efficient and secure mobility support in 6LoWPAN networks - Qiu, Yue (2017)
The machine-to-machine (M2M) communication, which plays a vital role in the Internet of Things (IoT), allows wireless and wired systems to monitor environments and exchange the information among various machines automatically without human interventions. In future, M2M communication could make many possible applications, such as e-health, smart grids, industrial automation and environmental monitoring, to produce various wide markets with many opportunities and to bring many more benefits to humans. To promote the development of the IoT and exploit the M2M applications, the Internet Engineering Task Force (IETF) has been developing a standard named Internet Protocol version 6 (IPv6) over low-power wireless personal area networks (LoWPANs) (6LoWPANs) to enable millions of IP-based M2M sensing devices to connect to the open Internet. Since these 6LoWPAN devices are resource constrained in terms of power, memory and battery, traditional security mechanisms which ensure the data security cannot be directly applied. Moreover, due to the reason that the mobile nodes (MNs) would compose a considerable part of future M2M systems, the Proxy Mobile IPv6 (PMIPv6) has been devised by the IETF network-based localized mobility management (NETLMM) working group to manage the mobility of the MNs with limited resources. Along with its development, 6LoWPAN networks still face various security threats and trust crises. Due to the large number of interconnected devices in the communication network that are generally deployed in the unattended environment, security is a critical issue for 6LoWPAN networks. Although the 6LoWPAN standard and PMIPv6 protocol have specified many important issues, various security issues have not been addressed. Most of the existing solutions, which focus on the enhancement of the abilities to withstand malicious attacks, are designed for static nodes while the security schemes for protecting the MNs is almost a blank page. To fill up this gap, in this thesis, we first introduce the concept and the architecture of the 6LoWPAN in which some mobility support protocols proposed by the IETF can be implemented to realize nodes’ mobility. In particular, the security requirements and vulnerabilities in 6LoWPAN are addressed which are important criteria when designing a 6LoWPAN security mechanism. Based on the existing security issues in 6LoWPAN, several security schemes are proposed to enable 6LoWPAN devices to roam in the 6LoWPAN environment efficiently and securely. To meet the requirements of the future IoT that devices can access various network services whenever and wherever needed, supporting a large number of devices is a prerequisite. Therefore, these proposed schemes are designed to be able to provide secure mobility protections for a single node as well as a group of nodes. The logic correctness of the proposed schemes is proved by the protocol logic. The formal verification by the verification tools and the performance evaluation results show that the proposed security schemes for 6LoWPAN networks could not only enhance the security functionalities with the ability to prevent various malicious attacks but also be computationally efficient.